ANALISIS KEBIJAKAN PENGELOLAAN SAMPAH DI KOTA TANGERANG SELATAN - Ahmad Jamil Pasaribu; Muhammad Taslim; Abdur Rahim (LPSDI Bina Patria, 2024)
Waste production is a serious problem that affects cities all over the world. In the future, the population continues to increase and economic development will result in waste production increasing. Meanwhile, poor waste management resulting in very large amounts of waste being thrown into landfills will certainly shorten the lifespan of landfills, which of course can cause environmental problems, public health or disasters. This study aims to analyze waste mitigation policies in South Tangerang City using library research. The research results show that waste management in Tangerang City has not been effective in reducing waste disposed of in the landfill. This occurs because waste management procedures allow waste to be disposed of directly to the landfill without a prior selection process, as well as the limited number of TPS3R as waste selection sites. Therefore, the South Tangerang City government must develop strict waste management procedures by first selecting TPS3R. so that the waste that is sent to the landfill is only residue.